Community Empowerment in The Making of Empo-Empon Towards the Achievement of Independent Villages Resistant to Covid-19 - Defirson Defirson; Sabarudin Sabarudin; Sugiarti Sugiarti; Uce Lestari (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
In the village of Kumpeh Ulu, you can find various types of plants that are efficacious, one of which is spice plants such as ginger, turmeric, temulawak, galangal, and temu Kunci. The problem encountered in the village of Kumpeh Ulu is that there is limited knowledge regarding techniques for processing these spices into Simplicia, they do not yet know the innovation of food products into health drinks and snacks and the people's economy is still low. The use of medicinal plants there is still very simple, only carried out empirically based on the use and processing that has been passed down from generation to generation. Based on the above, the spice plants or Empon-Empon produced there can be processed into food products as a co-19-resistant immune system enhancer. Community Service (PKM) aims to process empon-empon which is commonly found in Kumpeh Ulu Village into effective innovations such as instant drinks, jelly candy, and marshmallows and can open employment opportunities for empowering and improving the economy of the Kumpeh Ulu Village community. The method in this PKM includes counseling regarding the benefits and nutritional content of Empon-Empon as well as demonstrations of making instant drinks, jelly candy, and marshmallows based on red ginger and areca nut. The PKM results obtained areca ginger instant drink products, areca ginger jelly candy, and areca ginger marshmallows which will be made into superior products of Kumpeh Ulu Village, Muaro Jambi. From the results of the monitoring and evaluation of PKM activities, it was found that the people of Kumpeh Ulu Village had produced jelly candy, instant drinks, and marshmallows in the joint business group in the Kumpeh Ulu village hall, Muaro Jambi Regency